CONTEMPORARY FATAWA OF NAHDLATUL ULAMA: Between Observing the Madhhab and Adapting the Context (State Islamic University (UIN) of Sunan Ampel Surabaya, 2011)
Fatwa in the circle of Nahdlatul Ulama (NU) remains showing reminiscent of classical period of Islamic jurisprudence. It uses madhhab and taqlid with the employment of classical jurisprudence texts. Being identical in certain crucial features, the NU’s version of fatwa, however, is different from classic fatwa in various aspects. Fatwa is collegial, binding and modern. This last aspect remains debatable within the NU. While senior ulama‘ resist the reintroduction of ijtihad in the process of fatwa issuing as a tradition which should be preserved, certain younger ulama‘ in the organization urges the employment of ijtihad to keep up with the demand of modern context. Senior ulama‘ of the NU maintain that taqlid and madhhab is the very essence of their commitment to Islamic law, whereas the younger ulama‘ assert that such attachment will only result in the abandonment of Islamic law altogether by Muslims, especially the NU members. This article shows that dynamic with special reference to what is happening in East Java, the traditional stronghold of the NU.